Development and assessment of ICT maturity and global competitiveness using a Two-Wheel causality model - Yunis, Manal M. (2009)
Most evidence of ICT impact is at the firm level; the global impact of ICT at the country level has not been studied and incorporated within an integrated theoretical framework. This paper contains the development of a model to depict the strategic impact of a country's ICT resources on global competitiveness. The Two-Wheel model is a symbolisation for a dynamic process where one wheel (a country's ICT maturity) pushes the other (global competitiveness). The model is based on literature review and study of models provided by previous researchers regarding the impact of ICT on the performance of international firms. Using theoretical frameworks and a quantitative method technique, the model will be both validated and assessed. The application of the model includes: (a) identification of the strategic ICT factors that would help countries attain better ranks in the global competitiveness spectrum; (b) examining the causality relationship between ICT maturity and global competitiveness; and (c) derivation of global competitiveness rankings for countries based on their ICT maturity levels.